Identification Of Benefits From Desktop Virtualization Implementation Using IS/IT Buiness Value Rantis Generic Model (A Case Study At Ukridaes Computer Laboratory) - Marcel, Marcel (Teknik dan Ilmu Komputer, 2017)
uThe use of IS/IT (Information Systems/Information Technology) is no longer seen merely as technical aids, but it has evolved into a strategic tools, as business enabler. UKRIDA (Universitas Kristen Krida Wacana)Ã¢â¬â¢s computer laboratory recently made investments to renew their computer from PC (Personal Computer) into virtual desktop. Since the resources required for the initiatives is quite significant, justification (benefits identification) is needed. Rantis Generic IS/IT Business Value was used as a model for identification of benefits. The identification process found 7 (seven) categories of benefits and 10 (ten) sub-categories of benefits. Furthermore, the relationship among the identified sub-categories became the basis for discovering two potential threats to the benefit, namely the aspect of service reliability and userÃ¢â¬â¢s knowledge.ÃÂ Keywords: identification of benefits, IS/IT, desktop virtualization, RantiÃ¢â¬â¢s Generic IS/IT, case study, university